الضمانات المالية في مجال الصفقات العمومية - طبي حمزة (جامعة المسيلة, 2021)
تكتسي الصفقات العمومية أهمية بالغة ومحورا أساسيا في تنفيذ مخططات التنمية، و دفع العجلة الاقتصادية، فهي بذلك تكلف الدولة مبالغ باهظة، كون أغلب النفقات تصرف في شكل صفقات بشتى أشكالها و أنواعها، لاسيما الموجهة لتنفيذ مشاريع ذات منفعة وطنية. و باعتبار الصفقات العمومية ذات صلة وثيقة بالخزينة العمومية، كان لزاما على التشريع الجزائري وضع منظومة قانونية متكاملة تفرض على المتعاقدين تقديم ضمانات مالية، تكفل بها توفير قدر من الحماية للمال العام من جهة و تحقق حسن تنفيذ الصفقة العمومية من جهة ثانية. Abstract: Financial Guarantees in the Field of Public Transactions Comparative Study Public transactions are very important and a key focus in the implementation of development plans, and the drive of the economic cycle. So, it costs the state large amounts, since most of the expenses are spent in the form of transactions in all its forms and types, especially those directed to implement projects of national benefit. And as the public transactions are closely related to the public treasury, it was necessary for the Algerian legislation to put an integrated legal system that requires contractors to provide financial guarantees, ensuring the provision of some protection for public money on one hand, and to achieve good implementation of the public transaction on the other hand.
Keywords: الضمانات المالية - الصفقات العمومية